Water level monitoring and controlling of water treatment plants using wireless sensors in LabVIEW - Obeed, Kamal Mushina (2018)
Monitoring and controlling systems are taken as the main entity of any field which can ensure for the effective performance, hence its importance is rising exponentially in industry field. There can be many factors which can bring variations in those systems. This may cease the efficiency of the industry and destruction of industrial equipment. Therefore, monitoring, evaluation and controlling of the variables of any system is significantly important. The main objective of this research is to investigate the process of combining monitoring and controlling of the water level in the distribution tanks of water treatment plants by using wireless sensors network. The design and developed prototype of remote monitoring and controlling system of water levels in various tanks can be used in different parts of the water treatment plants. We have proposed, developed and tested hardware module based on two Arduino Mega2560 boards linked wirelessly by using two NRF transceivers. Remote Arduino is designed to monitor the water flow and the level of the distribution tank besides controlling the water level whenever is necessary. The real time sensors readings obtained are observed by specially designed LabVIEW application using graphical user interface running on a PC connected directly to the local Arduino. The application displays and analyses sensors reading on the front panel. Water level is controlled based on preset values entered by the user. The experimental result and percentage error curve endorse the reliability and feasibility of the proposed system to provide a solution for similar problems in industrial liquids treatment process applications.